Covid- 19 Vaccines Apathy in Rural Nigerian Communities - AJAYI, OLUMIDE; AJAYI-OLUAJAYI, OLABISI (Acta Universitatis Danubius. Administratio, 2023)
The emergence of Covid -19 in Wuhan China, and its declaration as a global pandemic by the World Health Organization (WHO) raises series of concerns across different nations of the world. The discovery and massive production of vaccines to curb the scourge of the virus brought health sanity and relief to the world. Unfortunately, in a country like Nigeria with poor health infrastructure, and a poor doctor-patient ratio, the level of apathy towards Covid-19 vaccines remains high. This study examined apathy towards Covid-19 vaccines in rural Nigerian communities. The study employed the positivist approach of research design in which a survey was used to generate data. The findings indicate that family, friends, and acquaintances constituted the major source of information about Covid-19 vaccines, as only a few percent of the respondents received information on Covid-19 vaccines from health professionals. The data analyzed also shows that fear of side effects, the asymptomatic status of individuals, and perceived ineffectiveness of Covid-19 vaccines were the main reasons for apathy towards Covid-19 vaccines. The findings of the study also indicate the suitability of the Health Believe Model in understanding the health-seeking behavior of people in light of a global pandemic and worldwide vaccination intervention.